2020
DOI: 10.5194/wcd-1-247-2020
|View full text |Cite
|
Sign up to set email alerts
|

Subseasonal midlatitude prediction skill following Quasi-Biennial Oscillation and Madden–Julian Oscillation activity

Abstract: Abstract. The Madden–Julian Oscillation (MJO) is known to force extratropical weather days to weeks following an MJO event through excitation of stationary Rossby waves, also referred to as tropical–extratropical teleconnections. Prior research has demonstrated that this tropically forced midlatitude response leads to increased prediction skill on subseasonal to seasonal (S2S) timescales. Furthermore, the Quasi-Biennial Oscillation (QBO) has been shown to possibly alter these teleconnections through modulation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Anomalously high AR landfall activity was detected for certain MJO/QBO phase configurations at lead times of 3–5 weeks, and these anomalies persisted with decreasing lead time and eastward MJO propagation. Mayer and Barnes (2020), Mundhenk et al. (2018), and Nardi et al.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Anomalously high AR landfall activity was detected for certain MJO/QBO phase configurations at lead times of 3–5 weeks, and these anomalies persisted with decreasing lead time and eastward MJO propagation. Mayer and Barnes (2020), Mundhenk et al. (2018), and Nardi et al.…”
Section: Introductionmentioning
confidence: 98%
“…Anomalously high AR landfall activity was detected for certain MJO/QBO phase configurations at lead times of 3-5 weeks, and these anomalies persisted with decreasing lead time and eastward MJO propagation. Mayer and Barnes (2020), Mundhenk et al (2018), andNardi et al (2020) demonstrated that the predictability and magnitude of western U.S. AR activity and precipitation anomalies is especially enhanced during certain phase configurations of the MJO and QBO. These studies also revealed that including information about the QBO can significantly modify the empirical relationships between the MJO and AR activity and precipitation.…”
mentioning
confidence: 99%
“…Feng and Lin (2019) also suggest that enhanced midlatitude westerlies during the westerly QBO might enhance upward propagation of Rossby waves that then influence the NAO. Mayer and Barnes (2020) showed that prediction skill in the midlatitude atmospheric circulation is significantly enhanced associated with MJO events in strong QBO states, with especially enhanced skill during the westerly QBO.…”
Section: Introductionmentioning
confidence: 99%
“…NAO variability during winter is driven by numerous physical mechanisms including remote tropical forcing by the Madden-Julian Oscillation (MJO) (Ferranti et al 2018, Tseng et al 2018, Mayer and Barnes 2020 and ENSO (Ayarzagüena et al 2018, King et al 2018, Nie et al 2020, sudden stratospheric warmings (SSW) (Sigmond et al 2013, Tripathi et al 2015, Domeisen et al 2020, and eddymean dynamics of the zonal index (Gerber andVallis 2007, Hitchcock andSimpson 2016). These mechanisms may yield similar NAO-like patterns, but each operates over different, overlapping timescale ranges.…”
Section: Introductionmentioning
confidence: 99%